Logics in artificial intelligence : 16th European Conference, JELIA 2019, Rende, Italy, May 7-11, 2019, proceedings /: 16th European Conference, JELIA 2019, Rende, Italy, May 7-11, 2019, proceedings. (2019) - Unknown
No abstract available